2011
DOI: 10.2131/jts.36.817
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 6 is a molecular target for 1,2-naphthoquinone, an atmospheric electrophile, in human pulmonary epithelial A549 cells

Abstract: -1,2-Naphthoquinone (1,2-NQ) is an electrophile found in the atmosphere, which reacts readily with protein nucleophiles to form a stable protein adduct. Peroxiredoxin 6 (Prdx6) is predominantly expressed in lung tissue and functions in antioxidant defense by facilitating the repair of damaged cell membranes via reduction of peroxidized phospholipids. In the present study, human A549 pulmonary epithelial cells were exposed to 1,2-NQ to explore whether 1,2-NQ can bind covalently to Prdx6, thereby disrupting its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…The HO-1 expression was also similar to the result of the Nrf2 signaling activity (Figure 6b). A previous study demonstrated that the α,β carbonyl in 1,2-naphtoquintione is an electrophile that resulted in the nucleophile protein, Keap1, which is added to the carbon β by Michael addition [18]. A similar result was obtained, except for 3,4-dihydrocoumarin, which suggested that the α,β carbonyl in the molecule plays a significant role as an electrophile for the Nrf2 activator.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The HO-1 expression was also similar to the result of the Nrf2 signaling activity (Figure 6b). A previous study demonstrated that the α,β carbonyl in 1,2-naphtoquintione is an electrophile that resulted in the nucleophile protein, Keap1, which is added to the carbon β by Michael addition [18]. A similar result was obtained, except for 3,4-dihydrocoumarin, which suggested that the α,β carbonyl in the molecule plays a significant role as an electrophile for the Nrf2 activator.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, the pteryxin, as one of the main Nrf2 activators in the extract, dissociated the Nrf2 from Keap1, and then the Nrf2 translocated into the nucleus, activated the ARE region containing the promoter and enhancer regions-mediated antioxidant enzyme, HO-1 (Figures 3-5). Some α,β carbonyls in the molecule will be potential electrophiles that react with the nucleophile protein, Keap1 [18]. When the cysteine residue in the Keap1 is oxidized by an electrophile, the Nrf2 part from Keap1 binds to the ARE region in the DNA sequences.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 1,2-NQ inhibits LPS-mediated IKKβ/NFκB/ iNOS signaling presumably through electrophilic modifi - cation of IKKβ (Sumi et al, 2010) and CREB/Bcl-2 signaling is disrupted by exposure to a higher concentration of 1,2-NQ through S-arylation of CREB through Cys286 (Endo et al, 2007(Endo et al, , 2011. We previously reported that 1,2-NQ covalently modifies peroxiredoxin 6, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and ubiquitin carboxyl-terminal hydrolase L1 (UCH-L1) via their thiol groups (peroxiredoxin 6, Cys47 and Cys91; GAPDH, Cys152; UCH-L1, Cys152), leading to inhibition of their enzyme activities (Takayama et al, 2011;Miura et al, 2011a;. These S-arylations are restored by addition of DTT or GSH, leading to recovery of the activities.…”
Section: Covalent Modifi Cation Of Proteins By 12-naphthoquinonementioning
confidence: 99%
“…With GAPDH, a subsequent examination revealed that the unique reaction is attributable to a GSH-dependent S-transarylation mechanism (Kumagai and Abiko, 2017). Although it was also shown that 1,2-NQ can modify lysine residues in proteins, a study with UCH-L1 clearly revealed that N-arylations of this protein through Lys4 are unaffected by addition of GSH (Takayama et al, 2011;Toyama et al, 2014). We also reported that the irreversible N-arylation of 1,2-NQ at Lys85 on Trx inhibits its activity, resulting in activation of Trx/ASK1 signaling associated with apoptotic cell death (Hirose et al, 2012).…”
Section: Covalent Modifi Cation Of Proteins By 12-naphthoquinonementioning
confidence: 99%
“…Using anti-1,2-NQ, it has been demonstrated that protein tyrosine phosphatase 1B (PTP1B) (Iwamoto et al, 2007), cAMP response element-binding protein (Endo et al, 2007), inhibitory κB kinase β (Sumi et al, 2010), Kelch-like ECH-associated protein 1 (Keap1) (Miura et al, 2011c), glyceraldehyde-3-phosphate dehydrogenase (Miura et al, 2011a(Miura et al, , 2011b, peroxiredoxin 6 (Takayama et al, 2011) and thioredoxin1 are molecular targets of 1,2-NQ for covalent modification. More importantly, it has been shown that activations of epidermal growth factor receptor and NF-E2-related factor 2 (Nrf2) are attributable to S-arylation of PTP1B through Cys121 and of Keap1 through Cys151 by 1,2-NQ, respectively (Iwamoto et al, 2007;Kobayashi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%